If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x-2=7x-14
We move all terms to the left:
10x-2-(7x-14)=0
We get rid of parentheses
10x-7x+14-2=0
We add all the numbers together, and all the variables
3x+12=0
We move all terms containing x to the left, all other terms to the right
3x=-12
x=-12/3
x=-4
| x^2-3x=16x+60 | | 7=9-2a | | 11x+9=5x-27 | | 2(x-5)=-3x+3 | | -1(2x-3)=11 | | x2=81144 | | x+11/4=-5/8 | | 9x+9(6)=36 | | +2M)+y(–1N)=0 | | 10x+70=160 | | 1+6g=2(g+2) | | x2=9/4 | | 6x+18=-54 | | 2z+7=7z+2 | | 8x+4=-3x+15 | | 2z+7=7z-2 | | 3.1+10m=7.26 | | 36=17+b+17 | | 4s+11=70 | | 7-8W=-5w-9 | | (4x-3)=5x-18 | | 8x+4=-3x+6+11x | | 3x+10x+15x=30 | | 2z+13=60 | | 8x+4=-3x+4+11x | | 1-x^-2=0 | | X^2-18x+83=-3 | | 4r+11=6r-3 | | 11–7x=67 | | 5c+1=51 | | 6y+2=74 | | 8x+3x=36 |